Performance improvement of induction motor drive using simplified FLC method - Talib, Md Hairul Nizam; Ibrahim, Zulkifilie; Abd Rahim, Nasrudin; Abu Hasim, Ahmad Shukri; Zainuddin, Hidayat (2014)
This paper presents the improvement method for simplified Fuzzy Logic Controller (FLC) for Induction Motor Drive. This method is aimed to enhance performance for variable speed drive performance in a rated forward and reverse operation. The implementation of simplified rules based is able to reduce the computational burden and memory space limitation. However, the speed performance shows some degradation with regards to simplification process. Thus, the propose improvement method is made to increase the error gain parameter. The membership function (MF) domain for error is increased from nominal 1 to 2. It increases the torque current and improves the speed response. The speed control is applied to the indirect Field Oriented Control method fed with Space Vector Pulse Width Modulation (SVPWM). The real time implementation is done using dSPACE DS1103 controller. The performance results are compared between simplified rules method, simplified rules improvement method and Anti-Windup Proportional Controller (AWPI). The results show improvement in terms of rise time, overshoot and settling time compared to its counterparts.